Potential mechanism of the Shunaoxin pill for preventing cognitive impairment in type 2 diabetes mellitus - Guo, Yuejie; Luo, Ning; Kang, Xueran (Frontiers in Neurology, 2022)
Objective: To analyze the efficacy and mechanism of action of the Shunaoxin pill in preventing cognitive impairment in diabetic patients by using network pharmacology. Methods: The main active compounds of the Shunaoxin pills and their targets of action were identified via the TCMSP and Batman-TCM databases. The GEO database was used to identify the genes in type 2 diabetic individuals that are associated with cognitive impairment. Subsequently, a common target protein-protein interaction (PPI) network was constructed using the STRING database, and targets associated with diabetes and cognitive impairment were screened by performing a topological analysis of the PPI network. AutoDock Vina software was used for molecular docking to evaluate the reliability of the bioinformatic analysis predictions and validate the interactions between active ingredients of shunaoxin pill and proteins associated with diabetes and cognitive impairment. Results: Based on the TCMSP and Batman-Tcm platform, 48 active ingredients of the Shunaoxin pill were identified, corresponding to 222 potential action targets. Further analysis revealed that 18 active components of the Shunaoxin pill may contribute to cognitive impairment in type 2 diabetic patients. Molecular docking simulations demonstrated that the active ingredients of the Shunaoxin pill (hexadecanoic acid, stigmasterol, beta-sitosterol, and angelicin) targeted four core proteins, OPRK1, GABRA5, GABRP, and SCN3B. Conclusion: Active ingredients of the Shunaoxin pill may alleviate cognitive impairment in diabetic patients by targeting the proteins OPRK1, GABRA5, GABRP, and SCN3B.